If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 4x + 3 + -2x = 4 + 4x + 5 + -3x Reorder the terms: 6 + 3 + 4x + -2x = 4 + 4x + 5 + -3x Combine like terms: 6 + 3 = 9 9 + 4x + -2x = 4 + 4x + 5 + -3x Combine like terms: 4x + -2x = 2x 9 + 2x = 4 + 4x + 5 + -3x Reorder the terms: 9 + 2x = 4 + 5 + 4x + -3x Combine like terms: 4 + 5 = 9 9 + 2x = 9 + 4x + -3x Combine like terms: 4x + -3x = 1x 9 + 2x = 9 + 1x Add '-9' to each side of the equation. 9 + -9 + 2x = 9 + -9 + 1x Combine like terms: 9 + -9 = 0 0 + 2x = 9 + -9 + 1x 2x = 9 + -9 + 1x Combine like terms: 9 + -9 = 0 2x = 0 + 1x 2x = 1x Solving 2x = 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 1x + -1x Combine like terms: 2x + -1x = 1x 1x = 1x + -1x Combine like terms: 1x + -1x = 0 1x = 0 Divide each side by '1'. x = 0 Simplifying x = 0
| 2/3y=26 | | 5.3=u | | 50=sqrt(3x) | | 4a-7a+10-15= | | tanx=-0.5x | | 2x+21+3x-4=55-3x+34 | | 22=4u-6 | | m/6=20 | | F(x)=36x^3+51x^2-42x-45 | | f(x)=3x^2+12x-7 | | 45-1.75n=2.25n-11 | | 3x+7y=c | | 1.5(x-5)=9.6 | | 5x^2-42x+27=0 | | 12(5+3x)=240 | | 4x+4=12-x | | (-2x^2)-x+2=0 | | Z=-3x+3y+5 | | 25n^2-24n+16=0 | | 2x^2+4px+p^2-p+2=0 | | M-1/2=(-5/4) | | 4x-1+113=180 | | 6(7x+5)=2130 | | 2x+25=12+15 | | 5x-50=5x+50 | | 3b+4b+7-3= | | 70+50+x+25=180 | | 9y+4=5(y-4) | | 5x+50=5x+50 | | 8(6x-5)=4760 | | y-4=1/2(x-15) | | -2.5+1.5y=11-3y |